EVALUASI PROGRAM AREA TRAFFIC CONTROL SYSTEM DALAM MENURUNKAN PELANGGARAN LALU LINTAS DI KABUPATEN SUMEDANG - Sulastri, Lalas; Ediyanto; Rusmayanti, Dedeh; Suryana, Yayat; Fardiansyah, Muhamad Nizar; Setiadi, Tatang (JRPA - Journal of Regional Public Administration, 2024)
This study aims to evaluate the ATCS Program in reducing traffic violations in Sumedang Regency. The method used in this research is qualitative. The target of the study is 63 individuals, with five informants consisting of the Secretary of the Department of Transportation, the Head of the Safety and Supervision Division, the Head of the Safety Section, an ATCS Operator, and an ATCS Technician. Data collection techniques include data reduction, data presentation, conclusion drawing/verification, and triangulation. The results of the study regarding the evaluation of the ATCS program in reducing traffic violations in Sumedang Regency from the implementation perspective can be considered quite good, but there is still a lack of infrastructure, which has led to no significant decrease in traffic violations in Sumedang Regency. From the impact perspective, it is also considered good, with many people becoming more orderly in driving, especially at intersections with ATCS cameras. The recommendations from this study include improving infrastructure, imposing penalties on traffic violators, and increasing human resources to help the ATCS program reduce traffic violations in Sumedang Regency.